Harvesting energy from moving vehicles with single-axis solar tracking assisted hybrid wind turbine. (2020) - Hemanth Kumar, D.; Krishna, Ram; Dinesh Kumar, M.; Pradhan, Raghuram; Sreenivasan, M.
Abstract: Renewable energy is a reliable and practical option for generating electricity and is considered one of the key ways to reduce environmental impact. There have been concentrated efforts devoted to next-generation technology to enhance performance, reliability and future growth of wind energy. However, there is always been concern about wide and bulky horizontal axes of wind turbines. Recent developments in wind turbine technology, particularly in the case of vertical axis wind turbines have shown that they are more adaptable to utility-scale power plants. As the energy generates from wind flow in both directions, we used this concept to model a novel hybrid wind turbine to demonstrate energy harvesting viability in a controlled way entirely from the moving vehicles on highways, with a three-bladed wind turbine and a solar tracking system. The hybrid wind turbine provided more energy and better efficiency in comparison to traditional wind turbines on the highways.